Laplacian Operator as Speaker Identification Parameter - Jamil, S. K. (Iraqi Journal of Physics, 2009)
New speaker identification test’s feature, extracted from the differentiated form of the wave file, is presented. Differentiation operation is performed by an operator similar to the Laplacian operator. From the differentiated record’s, two parametric measures have been extracted and used as identifiers for the speaker; i.e. mean-value and number of zero-crossing points.